Digging Deeper Into the Culture of Writing: Do Mentor Texts Inspire Male Students to Write? - Natalie Judith Gericke; Lindsay Gloria Salmon (Networks: An Online Journal for Teacher Research, 2013)
In a growing trend in schools across the country, girls are out-performing boys in the area of literacy. Some researchers would support a disconnection regarding specific topics taught in the literacy curriculum and the interests of boys (Gurian & Stevens, 2004). In our kindergarten and first grade classrooms, we have observed a difference in the participation between boys verses girls during writer’s workshop. In this article, we share our experiences, as two primary teachers, in utilizing mentor texts and mini-lessons to teach writing to our male kindergarten and first grade students. We will share research on Early Emergent literacy and gender within the classroom. We discuss our findings on how infusing mentor text into writer’s workshop mini-lessons motivated our male students to write using author’s craft. The research and our findings helped us answer the question: How can we use mentor texts and teacher guided mini-lessons to help kindergarten and first grade boys use author’s craft in their writing to show expression? The goal of this article is to provide early childhood educators examples of writing lessons using mentor texts that will motivate male students to write.